Dual-band performance enhancement of terahertz patch antennas via slotting method - Bich Ngoc Tran-Thi; Trong Hai Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Sixth-generation (6G) wireless networks are designed to provide ultra-high data rates with latencies as low as one microsecond, operating at frequencies higher than those used in fifth-generation (5G) networks. This study focuses on a compact and flexible dual-band terahertz (THz) rectangular patch antenna utilizing a slot cutting technique. The antenna features strategically placed rectangular slots on its patch, with dimensions of 1×1×0.1 mm. Its performance was simulated using computer simulation technology (CST) Studio Suite simulation software. The results indicate that the antenna operates at frequencies of 147.42 GHz and 202.5 GHz, achieving gains of 2.66 dB and 4.52 dB, respectively. Notably, the designed antenna demonstrates excellent impedance matching, as evidenced by deep return loss values of −19.818 dB and −44.776 dB. Furthermore, the findings report a voltage standing wave ratio (VSWR) of 1.01. This antenna design is suitable for applications in aerospace, 5G handheld devices, wireless communication, and THz medical imaging.